Architecture and Chiasmus. The resonance of landscape (2015)
Abstract Focusing on the presence of Nature, regardless of scale or dimension (a park, a small garden, or a tree), and regarding the individual inhabiting a house or a room, his dwelling, we intend to discuss how landscape implies in architecture the assumption of space as simultaneously ‘outside’ and ‘inside’. The theoretical framework we rely upon in this issue is Phenomenology, namely based on Merleau-Ponty‘s approach to perception (Phénoménologie de la Perception [The Phenomenology of Perception], L’Oeil et l’Esprit [Eye and Mind], Le Visible et l’Invisible [The Visible and the Invisible]), and the phenomenological understanding of architecture (through Steven Holl, Peter Zumthor, Juhani Pallasmaa, David Seamon). Within this scope, we debate to what extent Merleau-Ponty’s L’Entre-deux (In-Between), and subsequent ontology of the sensible, deals with landscape as a category towards the constitution of a subjective experience of space and time. The ‘outside’ is not the world exercising the ego possibilities, but the primordial experience involving the individual and the world. Iconic examples as the Fallingwater House (Frank Lloyd Wright), the Glass House (Lina Bo Bardi), and the Farnsworth House (Mies van der Rohe) are employed to interpret landscape’s contribution towards the understanding of a descriptive ontology of the visible-invisible, and to unfold the meaning of Chiasmus.